Economics of adding fat and increasing lysine:calorie ratio in diets for growing-finishing gilts - De La Llata, M.; Langemeier, Michael R.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,200 gilts was used to evaluate the economics ofadding fat and increasing lysine:calorie ratio in diets for growing-finishing pigs. Diets were fed in four phases and consisted of a 2 x 4 factorial arrangement with two levels of fat (0 and 6%) and four increasing lysine:calorie ratios. Eight economic scenarios combining com, soybean meal, fat, and hog prices with two packer grading systems were created. Stochastic dominance analysis was performed on 64 alternatives (8 treatments x 8 scenarios). The third "and fourth (higher) lysine: calorie ratios increased income over feed cost when fat was added to the diets, except for the high fat price scenario in which the fourth lysine:calorie ratio without added fat dominated. The first two (lower) lysine: calorie ratios were inferior under all scenarios.
Keywords: Swine; Lysine:calorie ratio; Fat; Lysine; Finishing pigs; Economics